2019
DOI: 10.1038/s41598-019-46004-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, Clinical and Genetic Study of Hypophosphatasia in A Spanish Population: Identification of Two Novel Mutations in The Alpl Gene

Abstract: Hypophosphatasia (HPP) is a genetic disease caused by one or several mutations in ALPL gene encoding the tissue-nonspecific alkaline phosphatase affecting the mineralization process. Due to its low prevalence and lack of recognition, this metabolic disorder is generally confused with other more frequent bone disorders. An assessment of serum total alkaline phosphatase (ALP) levels was performed in 78,590 subjects. Pyridoxal-5′-phosphate (PLP) concentrations were determined and ALPL gene was sequenced in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 36 publications
1
31
1
2
Order By: Relevance
“…By Sanger sequencing approximately 95% of all mutations in ALPL can be detected ( Mornet, 2000 ; Taillandier et al, 2015 ). Compared to previous studies ( García-Fontana et al, 2019 ; Maman et al, 2016 ; Riancho-Zarrabeitia et al, 2016 ; Tornero et al, 2020 ), we also included MPLA for detection of deletions and duplications and found one patient with a large deletion of exon 2, indicating that MLPA should be considered in patients with signs of HPP and normal Sanger sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…By Sanger sequencing approximately 95% of all mutations in ALPL can be detected ( Mornet, 2000 ; Taillandier et al, 2015 ). Compared to previous studies ( García-Fontana et al, 2019 ; Maman et al, 2016 ; Riancho-Zarrabeitia et al, 2016 ; Tornero et al, 2020 ), we also included MPLA for detection of deletions and duplications and found one patient with a large deletion of exon 2, indicating that MLPA should be considered in patients with signs of HPP and normal Sanger sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the greater parental concern about short stature in sons versus daughters may be one of the explanations for the higher proportion of males in pediatric HPP patients. It is worth noting that contrary to the pediatric HPP, a higher proportion of females than males was observed in adult HPP [ 14 , 19 21 ]. Considering the small number of pediatric HPP patients diagnosed in our country, the sex differences observed in the current study still need to be verified in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the greater parental concern about short stature in sons versus daughters may be one of the explanations for the higher proportion of males in pediatric HPP patients. It is worth noting that contrary to the pediatric HPP, a higher proportion of females than males was observed in adults diagnosed with HPP [13,[18][19][20]. Considering the small number of pediatric HPP patients diagnosed in our country, the sex differences observed in the current study still need to be veri ed in further studies.…”
Section: Discussionmentioning
confidence: 67%